The effect of whole egg intake on muscle mass: Are the yolk and its nutrients important? - Santos, H. O.; Gomes, G. K.; Schoenfeld, B. J.; de Oliveira, E. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Whole egg may have potential benefits for enhancing muscle mass, independent of its protein content. The yolk comprises 40% of the total protein in an egg, as well as containing several nonprotein nutrients that could possess anabolic properties (e.g., microRNAs, vitamins, minerals, lipids, phosphatidic acid and other phospholipids). Therefore, the purpose of this narrative review is to discuss the current evidence as to the possible effects of egg yolk compounds on skeletal muscle accretion beyond those of egg whites alone. The intake of whole egg seems to promote greater myofibrillar protein synthesis than egg white intake in young men. However, limited evidence shows no difference in muscle hypertrophy when comparing the consumption of whole egg versus an isonitrogenous quantity of egg white in young men performing resistance training. Although egg yolk intake seems to promote additional acute increases on myofibrillar protein synthesis, it does not seem to further enhance muscle mass when compared to egg whites when consumed as part of a high-protein dietary patterns, at least in young men. This conclusion is based on very limited evidence and more studies are needed to evaluate the effects of egg yolk (or whole eggs) intake on muscle mass not only in young men, but also in other populations such as women, older adults, and individuals with muscle wasting diseases.